تصنيع مشروب جديد من بذور الخرنوب (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
بينت هذه الدراسة، أنه يمكن تصنيع مشروب جديد مغذي بنكهة مرغوبة من بذور الخرنوب، وذلك بتحميص بذور الخرنوب الطازجة على درجة حرارة 200 C° لمدة 2min.بينت الاختبارات الحسية واختبار التذوق وفقاً لمعايير الجودة العالمية ISO85887:2005 على عينات المشروب المحضرة من بذور محمصة على درجات حرارة وأزمنة مختلفة أن عينة المشروب المحضر من بذور محمصة على درجة حرارة 200 C° لمدة 2min هي الأكثر ملائمة من الناحية الحسية، كما بينت نتائج التحليل الكيميائي لمسحوق بذور الخرنوب المحمصة على درجة حرارة 200 C° لمدة 2min المستخدم في تحضير المشروب أنه ذو قيمة غذائية عالية نظراً لمحتواه الجيد من البروتين19.8% والألياف12.9%، وانخفاض محتواه من اللبيدات إلى 1.6% والسكريات إلى1.5 %، وهو خال تماما من الكافيئين، بالتالي يمكن اعتماده كمشروب مغذي وصحي مناسب لمرضى القلب والسكري، وأن تصنيع هذا المشروب غير مكلف اقتصادياً.The study showed that We can Processing of a new pleasant nourishing drink from carob seeds, by roasting the fresh seeds of Carob at 200C° for 2 min. The results of sensory tests and test taste according to international quality standards ISO85887: 2005 at samples drink prepared from seeds roasted at different temperatures and times showed that the sample prepared at 200C° for 2min is the best, also the results of chemical analysis for powder of roasting carob seeds at 200C° for 2 min that used in prepare the drink showed that it has a high nutritional value because of its high content of protein 19.8% and fiber 12.9%, low content of fat to 1.6% and sugar to 1.5%, and completely free of caffeine, therefore, it suitable as a healthy and nourishing drink for patients with heart and diabetes disease. The manufacture of this drink is economically.